2009
DOI: 10.1128/jcm.00508-09
|View full text |Cite
|
Sign up to set email alerts
|

Cephalosporin MIC Distribution of Extended-Spectrum-β-Lactamase- and pAmpC-Producing Escherichia coli and Klebsiella Species

Abstract: The acquisition of ␤-lactamases in members of the Enterobacteriaceae family poses a challenge to antimicrobial susceptibility testing in the clinical laboratory. We correlated the distribution of the MICs for Klebsiella spp. and Escherichia coli with the presence of extended-spectrum ␤-lactamase (ESBL) and plasmid-mediated AmpC ␤-lactamase (pAmpC) genes. A total of 264 isolates were subjected to cefazolin, ceftriaxone, cefotaxime, ceftazidime, cefepime, and aztreonam agar dilution MIC determination; ESBL scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…A recent study showed that when the revised CLSI breakpoints were applied to 264 isolates of E. coli and Klebsiella species, the rates of susceptibility to cefotaxime and ceftazidime were reduced by 8% and 3%, respectively [11]. Similarly, we found that the revised susceptibility breakpoint criteria led to little change in the rates of susceptibility of cefotaxime (0.9%) and ceftazidime (3.0%) to Enterobacteriaceae producing AmpC β-lactamase.…”
supporting
confidence: 64%
“…A recent study showed that when the revised CLSI breakpoints were applied to 264 isolates of E. coli and Klebsiella species, the rates of susceptibility to cefotaxime and ceftazidime were reduced by 8% and 3%, respectively [11]. Similarly, we found that the revised susceptibility breakpoint criteria led to little change in the rates of susceptibility of cefotaxime (0.9%) and ceftazidime (3.0%) to Enterobacteriaceae producing AmpC β-lactamase.…”
supporting
confidence: 64%
“…According to the Clinical Laboratory Standards Institute (CLSI) recommendations, routine antimicrobial susceptibility testing should include screening for ESBL production, employing cefpodoxime, ceftazidime, aztreonam, cefotaxime, or ceftriaxone followed by phenotypic confirmation for the positive cases, based on demonstrating the effectiveness of the screening antibiotic in the presence of a beta lactamase inhibitor [11,12,13]. Results are issued with the aim of preventing inappropriate use of cephalosporins or monobactams in the setting of ESBL production [12].…”
Section: Introductionmentioning
confidence: 99%
“…The current European Committee on Antimicrobial Susceptibility Testing (EUCAST) and Clinical and Laboratory Standards Institute (CLSI) susceptibility breakpoints for cefepime are 1 µg/mL and 8 µg/mL (accounting for drug dosing), respectively [22,23]. There is concern that the current CLSI cefepime breakpoint leaves some ESBL enzymes in the susceptible range (ie, "hidden resistance)" [24].…”
Section: Cefepimementioning
confidence: 99%